Correlation between level of knowledge and attitude toward human papillomavirus vaccine in high school students - Adrianzén Peralta, Ana L. (2022)
Objective: To determine the correlation between level of knowledge and attitude toward human papillomavirus (HPV)vaccine in high school students. Materials and methods: An observational, descriptive, cross-sectional and prospective study. The population consisted offourth- and fifth-year female high school students. The research variables were level of knowledge of HPV and attitudetoward its vaccine. A previously prepared and validated knowledge survey and a Likert scale attitude test sheet wereused as instruments. For the statistical analysis, an Excel database was created. Then, the resulting information was processed in the IBM SPSS Statistics statistical software, applying Spearman’s Rho with a value of p < 0.05 to determine the correlation of the main study variables. The research was carried out with the educational institution's consent, parentalconsent and children’s assent.Results: A good level of knowledge of HPV prevailed in the students (75.45 %), followed by an intermediate level (21.82 %) and a poor level (2.73 %). Regarding the attitude, it was favorable in 12.73 %, indifferent in 52.72 % and unfavorable in 34.55 %. The correlation between attitude and level of knowledge was not statistically significant (p > 0.05).Conclusions: Most students have a good level of knowledge of HPV, which is not related to the attitude toward thevaccine, which shows a high percentage of indifference.